Research Trends in Mobile Learning - Yıldız, Gizem; Yıldırım, Abdurrahman; Akça, Bedreddin Ali; Kök, Ayşe; Özer, Açelya; Karataş, Serçin (International Review of Research in Open and Distributed Learning, 2020)
A total of 1023 selected articles published in 2016–2019 related to mobile learning were examined and classified according to the categories in this research: 40% of these articles used quantitative approaches, 18% of them used mixed, and 13% of them were literature reviews. The published studies were analyzed according to research model, sample size, sample level, learning fields, subject-area classification, data collection tool, data analysis technique, dependent variable, independent variable, mobile device, number of authors, and publication year. The findings were analyzed and interpreted as a percentage and frequency. This research will be useful for reviewing current research trends related to mobile learning studies, indicating potential research on the topics, and revealing the needs of the field.